Efficacy of Synbiotics in Patients with Slow Transit Constipation: A Prospective Randomized Trial - Ding, Chao (Nutrients, 2016)
Synbiotic intake may efficiently restore the balance of gut microbiota and improve gastrointestinal functions. The aim of the study was to evaluate the efficacy of a synbiotic in patients with slow transit constipation. A total of 100 patients with slow transit constipation were randomized to receive either a synbiotic or placebo twice daily for 12 weeks. The primary efficacy endpoints were the clinical remission and improvement rates at weeks 4 and 12. Stool frequency and consistency, colonic transit time (CTT), evacuation and abdominal symptoms, patient assessment of constipation symptoms, gastrointestinal quality-of-life index scores, satisfaction scores, and adverse events were also monitored. The clinical remission rates reached 37.5% at week 4 and 45.8% at week 12 in the treatment group, compared to 13.3% at week 4 and 16.7% at week 12 in the placebo group (p < 0.01 for both comparisons). Over 12 weeks, 64.6% of the patients who received the synbiotic experienced clinical improvement, compared to 29.2% of the patients in the placebo group (p < 0.01). During the intervention period, patients who were treated with the synbiotic exhibited increased stool frequency, improved stool consistency, decreased CTT, and improved constipation-related symptoms. This randomized, placebo-controlled trial suggested that dietary supplementation with a synbiotic improved evacuation-parameters-associated symptoms and colonic motility in patients with slow transit constipation (STC).